1997
DOI: 10.1038/ki.1997.424
|View full text |Cite
|
Sign up to set email alerts
|

Urine and plasma levels of uroguanylin and its molecular forms in renal diseases

Abstract: Uroguanylin activates the intestinal and possibly the renal guanylate cyclase C receptor, and stimulates Cl- secretion. We developed a sensitive radioimmunoassay (RIA) for human uroguanylin and measured its concentration in the urine and plasma. Twenty-four-hour urinary excretion of immunoreactive (ir-) uroguanylin for persons with a high-salt diet (10 g/day) was 137.8 +/- 14.4 pmol/day, significantly higher than that for persons with a low-salt diet (7 g/day, 95.1 +/- 16.3 pmol/day, P < 0.05). There were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 24 publications
4
92
0
1
Order By: Relevance
“…More than 11 yr ago, Nakazato et al (82) showed that human GN increases in patients who have chronic renal failure and undergo hemodialysis. The UGN concentration in plasma and/or in urine is increased in patients with chronic renal failure and glomerulonephritis and in patients on hemodialysis (52,(83)(84)(85). In patients with nephrotic syndrome, UGN plasma concentration was higher and urinary concentration was lower compared with values in healthy volunteers (84).…”
Section: Guanylin Peptides In Pathophysiologymentioning
confidence: 92%
See 2 more Smart Citations
“…More than 11 yr ago, Nakazato et al (82) showed that human GN increases in patients who have chronic renal failure and undergo hemodialysis. The UGN concentration in plasma and/or in urine is increased in patients with chronic renal failure and glomerulonephritis and in patients on hemodialysis (52,(83)(84)(85). In patients with nephrotic syndrome, UGN plasma concentration was higher and urinary concentration was lower compared with values in healthy volunteers (84).…”
Section: Guanylin Peptides In Pathophysiologymentioning
confidence: 92%
“…UGN is expressed in the kidney, and its expression is higher in animals that are on a high-salt diet (53,54). It is still not clear whether the increase in the urinary concentrations of UGN and cGMP (52,53) are due to local production and secretion of UGN within the kidney or to filtration in the glomerulus. Both GN and UGN circulate in the plasma and can be filtered in the glomerulus into the primary urine.…”
Section: Signaling Mechanisms Of Guanylin Peptides In the Kidneymentioning
confidence: 98%
See 1 more Smart Citation
“…The plasma uroguanylin correlated with serum creatinine (r = 0.71, P < 0.001). 10 A different study found that a diet high in salt leads especially to increased guanylin secretion (3 times), less uroguanylin secretion. Also the application of hyperosmolar manitole leads to a smaller, but still significant increase in guanylin secretion.…”
Section: -8 Measurement Of Guanylin and Uroguanylin In Humansmentioning
confidence: 99%
“…kidney or liver). 3,10 EFFECTS OF GUANYLIN AND UROGUANYLIN Uroguanylin and guanylin are peptides which influence the production of cGMP in enterocytes (and other tissues -see above) by activation of apical membrane, when the activation of guanylat cyclase takes place. Presumably these hormones play a role in the so-called "intestinalkidney axis", which directly influences the regulation of salt and water homeostasis.…”
Section: Guanylin Receptorsmentioning
confidence: 99%